The Role of Learning Media in Educational Components to Enhance Students - Azhura, Phalosa Dea; Mustikasari, Aurellia; Laily, Cindy Aulia Nurul; Mahardika, I Ketut; Yusmar, Firdha; Firdausi, Soraya; Astuti, Sri Rezeki Dwi (International Journal of Education, Information Technology, and Others, 2024)
Learning media play an important role in education because they can accelerate and facilitate the teaching and learning process and increase its effectiveness. This article discusses the contribution of learning media to the education of students by improving understanding of material, stimulating motivation and encouraging active student participation. Learning media also support independent learning by allowing students to access materials anytime and anywhere, extending learning beyond the classroom. Different types of media, ranging from traditional media such as books and posters to modern technologies such as digital simulations, interactive video and virtual reality, are used to meet different learning needs. The use of these media helps to overcome the physical limitations of classrooms and to accommodate students' learning styles, whether visual, auditory or kinesthetic. However, there are challenges such as limited infrastructure and lack of teacher skills in using technology. Solutions include ongoing teacher training and the development of locally appropriate media. With the right approach, learning media becomes a key element in achieving educational goals, not only educating students cognitively, but also developing character and life skills needed for the future. Learning media is not just a tool, but an essential factor in creating a holistic and sustainable education.